2007
DOI: 10.1111/j.1524-475x.2007.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced healing of mitomycin C‐treated wounds in rats using inbred adipose tissue‐derived stromal cells within an atelocollagen matrix

Abstract: The aim of this study was to evaluate the potential accelerating effects of an adipose tissue-derived stromal cells (ATSC)-containing atelocollagen matrix with silicone membrane (ACMS) for repairing mitomycin C-treated healing-impaired wounds. Mitomycin C was applied to full-thickness skin incisions in this study to create a healing-impaired wound model in rat. After thoroughly washing out the mitomycin C from the wound, ACMS alone or ATSC-containing ACMS was applied to the wounds. Histological sections of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 35 publications
1
61
0
2
Order By: Relevance
“…Preclinical and clinical studies with these cells have shown improvement in angiogenesis, 9 reduced inflammation, 10,11 and in other parameters associated with mechanism by which healing can be improved. 12,16 Recently, the United States Government has awarded Cytori Therapeutics, Inc., the developer of the Celution System, with a large research contract for evaluation of the system for potential use in patients with acute radiation exposure with concomitant thermal burn injury. 29 Specifically, the Biomedical Advanced Research and Development Authority (BARDA; a branch of the U.S. Department of Health and Human Services) awarded Cytori a research contract valued at up to US$106 million over 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical and clinical studies with these cells have shown improvement in angiogenesis, 9 reduced inflammation, 10,11 and in other parameters associated with mechanism by which healing can be improved. 12,16 Recently, the United States Government has awarded Cytori Therapeutics, Inc., the developer of the Celution System, with a large research contract for evaluation of the system for potential use in patients with acute radiation exposure with concomitant thermal burn injury. 29 Specifically, the Biomedical Advanced Research and Development Authority (BARDA; a branch of the U.S. Department of Health and Human Services) awarded Cytori a research contract valued at up to US$106 million over 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion has now been confirmed in a wide range of preclinical and clinical studies, including acute and chronic myocardial ischemia, 9,10 renal ischemia, 11 pulmonary hypertension, 12 bone, 13 intervertebral disc injury, 14 peripheral nerve regeneration, 15 and wound healing. 16 These cells have also been applied clinically in patients with heart attack, 17 breast reconstruction, 18 bone healing, 19,20 and wound healing. 21,22 In addition to eliminating the time and costs associated with clinical-grade cell culture, this approach generates a population of cells that is not comprised solely of ADSCs, but also includes a substantial number of other cell types with therapeutic potential, including vascular endothelial cells, tissue macrophages, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…In various pre-clinic studies, MSCs of adipose tissue origin have been used in various tissues in order to provide wound healing, and positive results have been obtained (20,21). Gimble et al have demonstrated how MSCs of adipose tissue origin activate the paracrine pathways with the cytokines and growth factors they release in the adipose tissue (22).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, exogenously administered human recombinant bFGF may target the ADRC and thus the improved scar may be enhanced. In animal models, although it is cultured, topical administration of adipose tissuederived stromal cells (ATSCs) is effective for rat cutaneous wounds induced by mitomycin C-treatment (16) and in diabetic mice wounds (17). Clinically purified autologous lipoaspirates were used as treatment for radiotherapy tissue damage of consecutive 71 patients.…”
Section: Discussionmentioning
confidence: 99%